2013
DOI: 10.2174/157016113805290317
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction in Sepsis

Abstract: The endothelium takes part in the regulation of numerous physiological functions and lies at the interface of circulating blood and the vessel wall. Under physiological conditions, it is responsible for anticoagulant and anti-adhesive properties, and it regulates vasomotor tone and vascular homeostasis. Endothelial dysfunction has been associated with many pathophysiological processes, such as inflammation and oxidative and nitrosative stresses. Endothelial cells are precociously exposed to circulating signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 80 publications
(94 reference statements)
4
46
0
3
Order By: Relevance
“…The understanding of underlying mechanisms of sepsis has been improving [15]. Inflammatory response, which is induced by sepsis, may cause serious organ dysfunctions where endothelial injury plays a pivotal role [16]. As well as being a gatekeeper between blood and tissues, endothelium also exerts many functions in anti-inflammatory and anti-oxidant defense.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The understanding of underlying mechanisms of sepsis has been improving [15]. Inflammatory response, which is induced by sepsis, may cause serious organ dysfunctions where endothelial injury plays a pivotal role [16]. As well as being a gatekeeper between blood and tissues, endothelium also exerts many functions in anti-inflammatory and anti-oxidant defense.…”
Section: Discussionmentioning
confidence: 99%
“…As well as being a gatekeeper between blood and tissues, endothelium also exerts many functions in anti-inflammatory and anti-oxidant defense. Bacterial toxins and oxidative stress disturb endothelial integrity [15,16]. This results in incresed permeability of the blood-brain barrier and brain edema, which may distort microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies done showed that endothelial dysfunction plays a key role in the pathophysiology of septic abortion (20) .…”
Section: Conditions Leading To Disseminated Intravascular Coagulationmentioning
confidence: 99%
“…Dysregulation of the innate immune system during sepsis leads to inflammatory signal amplification upon cellular recognition of bacterial products. Sepsis is characterized by abnormal leukocyte activation, severe endothelial injuries, and ultimately organ failure due to septic shock [1].…”
Section: Introductionmentioning
confidence: 99%